2007
DOI: 10.1142/s0219877007001053
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to Quality of Life: Cross-National Validation of New Metrics for Mobile Data Service Technology in Korea and Japan

Abstract: Every technology should be geared to improve the quality of users' lives. The important pre-requisite is to measure the contribution of the technology to quality of life reliably and validly. This study provides a theoretical and empirical basis for the development of better measures for the contribution of a mobile data service technology to the quality of users' lives. The reliability and validity were verified through online surveys in Korea and Japan. The survey results indicated that critical mobile data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(33 citation statements)
references
References 18 publications
0
30
3
Order By: Relevance
“…They propose that people actually experience and store the various events of their life in distinct domains, including leisure life, family life, friend life, cultural life, work life, community life, consumer life, financial life, health life, safety life, and self-life. These eleven life domains have been examined for mobile data services by Choi et al (2007a) concerning Japan and Korea. Our newly added life domains are educational life (Andrews andWithey, 1976, Choi et al 2007b), homehealthcare life (Jing and Andy, 2010), trustworthy life (Jing and Andy, 2010) and informational life (Nguyen et al, 2010) which are discussed below:…”
Section: Individual Life Domainsmentioning
confidence: 99%
See 4 more Smart Citations
“…They propose that people actually experience and store the various events of their life in distinct domains, including leisure life, family life, friend life, cultural life, work life, community life, consumer life, financial life, health life, safety life, and self-life. These eleven life domains have been examined for mobile data services by Choi et al (2007a) concerning Japan and Korea. Our newly added life domains are educational life (Andrews andWithey, 1976, Choi et al 2007b), homehealthcare life (Jing and Andy, 2010), trustworthy life (Jing and Andy, 2010) and informational life (Nguyen et al, 2010) which are discussed below:…”
Section: Individual Life Domainsmentioning
confidence: 99%
“…Moreover, we did not know yet which domains were most relevant to MIS in different countries and different users. Therefore, our study has investigated the following life domains from Choi et al (2007a), which have shown in Table 1.…”
Section: Individual Life Domainsmentioning
confidence: 99%
See 3 more Smart Citations